Application of psychological intervention combined with wet compress of Traditional Chinese Medicine in nursing of patients with diabetic foot ulcer (心理干预联合中药塌渍技术在糖尿病足溃疡护理中的应用) - WANG Xiuyan (王秀燕); CAO Hongjing (曹红京); LI Ning (李宁); LI Yueru (李月茹); LI Jing (李静); YANG Kun (杨坤); LI Lin (李林); TANG Hong (汤虹) (Association of Integrative Nursing, 2024)
Objective To evaluate the psychological intervention combined with Traditional Chinese Medicine Ta stain therapy in nursing of patients with diabetic foot ulcer. Methods Totally 64 patients with diabetic foot ulcer were randomly divided into the control group and the observation group, with 32 cases in each group. All patients received local dressing change in addition to the comprehensive treatment such as blood glucose control and infection prevention. Patients in the observation group were given psychological intervention combined with wet compress of Traditional Chinese Medicine. The condition of swelling relief and wound repair were evaluated after intervention, and the degree of pain was measured by using Visual Analogue Scale (VAS). Results The total effective rates of swelling relief and wound repair in the observation group were higher than those in the control group(P＜0. 05). The VAS score was decreased in both two groups after intervention, and VAS score in the observation group was lower than that in the control group(P＜0. 01). Conclusion The psychological intervention combined with wet compress of Traditional Chinese Medicine is effective to improve the swelling relief and wound repair, and reduce the pain of patients with diabetic foot ulcer. (目的 探讨心理干预联合中药塌渍技术在糖尿病足溃疡患者护理中的应用效果。方法 采用随机数字表法将64例糖尿病足溃疡患者分为对照组和观察组, 各32例。两组患者在积极控制血糖和抗感染的基础上, 给予局部换药; 观察组增加中药塌渍治疗, 并强化患者心理干预。评估患者红肿伤口消肿情况和破溃伤口修复情况, 采用视觉模拟评分(VAS)评估患者足部疼痛感, 评价干预效果。结果 红肿伤口消肿和破溃伤口修复评价结果显示, 观察组干预效果均优于对照组, 差异有统计学意义(P＜0. 05)。干预后, 两组VAS量表评分均较干预前下降, 且观察组VAS量表评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 在常规护理的基础上, 心理干预联合中药塌渍技术能有效促进糖尿病足溃疡患者红肿伤口消肿和破溃伤口的修复, 缓解足部疼痛感。)